Feeding practices and nutritional status of infant and young children on coastal and inland areas if the Fourth District of Camarines Sur, Philippines - Manrique, Jeena Sandra R.
IYCF practices significantly impact growth, development in early childhood, and long-term health status. This study investigates IYCF practices and the nutritional status of children aged 0-23 months in the fourth district of Camarines Sur. A total of 628 households with children aged 0-23 months participated in an analytical cross-sectional study employing a two-staged stratified random sampling design. Data on sociodemographic, economic factors, and IYCF practices were collected. Moreover, weight and length of the IYC were evaluated using the WHO Anthro Plus software. Descriptive statistics and multiple logistics regression were used in the analysis using R statistical software version 4.3.1.